Sobrevida e fatores prognósticos após Ressecção de Metástase Hepática Adenocarcinoma Calorretal - Renato Gomes Campanati (2018)
It is expected that half of the patients with colorectal adenocarcinoma will present with liver metastases, 20% being diagnosed at the same time as the primary tumor. Whenever feasible, liver resection presents with great improvement in survival in comparison to chemotherapy alone, varying between 24 and 64%. Although surgical treatment is superiorly known, patients with liver metastases are a very heterogeneous group. The aim of this study is to describe the overall survival in patients submitted to liver resection of colorectal metastases and to describe predictive prognostic clinical and pathological factors. Between January 2007 and August 2018, it was collected data relative to the epidemiology, the primary tumor, the liver metastases, the surgical procedure, the postoperative and pathologic results. The survival analysis was made using the Kaplan-Meier method and the comparison between curves with the log-rank test. The Cox regression model was used in the multivariate analysis. In the given period, it was obtained 84 hepatectomies due to colorectal metastases in 73 patients. The overall survival rate was 98,6%, 74,9% and 48,8% in 1, 3 and 5 years, respectively. The statistically significant factors after univariate analysis were tumor grade (p=0,050) and angiolymphatic invasion (p=0,021) in the colorectal tumor, synchronous metastases (p=0,020), as well as number (p=0,004), bilobar distribution (p=0,019) and greater diameter over 50mm (p=0,027) of the liver metastases. After multivariate analysis remained three independent factors of worst prognosis, which were: angiolymphatic invasion (HR=2,7; CI 95% 1,106 – 6,768; p=0,029), synchronous metastases (HR=2,8; CI 95% 1,069 – 7,365; p=0,036) and number of nodules greater than four (HR=1,7; CI 95% 1,046 – 2,967; p=0,033). The two-staged hepatectomy was an independent protective factor (HR=0,2; CI 95% 0,067 – 0,937; p=0,040). Thus, the resection of liver metastases of colorectal adenocarcinoma leads to higher survival rates and many prognostic factors, such as angiolymphatic invasion, synchronous metastases, four or more hepatic nodules and two-staged hepatectomy, may be used to predict prognosis and guide clinical decision making.